Carapaces of the Dnieper-Donets Basin as a New Exploration Target for significant hydrocarbon deposits - Т.О. Петровська; О.П. Петровський; О.М. Ціховська; А.Ю. Трачук (Геофизический журнал, 2022)
New geological structures — displaced blocks of salt overburden — were identified in the axial part of the Dnieper-Donets basin (DDB) beside one of the largest salt domes due to modern high-precision gravity and magnetic surveys and their joint 3D inversion with seismic and well log data.